Learning and Teaching in Secondary Schools - Ellis, Viv, 1965- (Exeter : Learning Matters, 2004)
Aimed at the professional reader, this text covers teaching and learning in secondary schools. It focuses on a range of key topics including learning styles, planning and assessment, inclusion and cross-curricular teaching.
Previous ed.: 2002.
Includes bibliographical references (p. 165-171) and index.
Keywords: Education, Secondary -- Great Britain; High school teaching -- Great Britain; Education